Side Stream End-Tidal CO2 Monitoring in Subjects Undergoing Non-Invasive Ventilation for Respiratory Failure: A Pilot Study - Nouwen, Marinus J.; Helmich, Elmar J. B.; Tjan, Dave H. T.; van der Steen, Marijke S. (Global Journal of Respiratory Care, 2016)
Purpose: End-tidal CO2 (PETCO2) is an important value to guide ventilation. For non-invasive ventilation (NIV) this is not always possible due to low flows. The Capnostream® monitor is able to measure PETCO2 in low flows. In this study the value of low flow PETCO2 measurement during non-invasive ventilation (NIV) will be assessed. A dimensionless number, provided by the Capnostream® monitor, to reflect respiration quality: the Integrated Pulmonary Index™ is also assessed. Methods: Subjects undergoing NIV were included. Repetitive PaCO2 values were matched with PETCO2 values in time. Correlation was assessed using Pearson’s R and Bland-Altman plots. IPI™ was recorded over time and analysed for trends over time. Results: Correlation between PETCO2 and PaCO2 was moderate to good. In the total group Pearson’s R was 0.75 (p < 0.001), for subjects with COPD 0.86 (p < 0.001) and for subjects without COPD 0.89 (p < 0.001). However, Bland-Altman plots show that the limits of agreement exceeded the predetermined acceptable variation. IPI™ analysis was hampered by large proportions of missing data. IPI™ was higher in non-COPD subjects and in subjects improving during ventilation. However, neither an incline was seen over time in subjects improving nor a decline in subjects deteriorating, while on NIV. Conclusion: Correlation between side-stream PETCO2 and PaCO2 was moderate to good, but showed a wide variation in Bland-Altman analysis and is therefore of only modest value in clinical practice. IPI™ analysis was hampered by missing data and did not have an additive value in standard clinical care.